Enhancing Critical Thinking using LCDS-Based Interactive Electronic School Book in Physics - Dian Pertiwi; Agus Suyatna; Eko Suyanto (Jurnal Pembelajaran Fisika, 2019)
This study aims to describe the effectiveness of interactive BSE utilization as a supplement for blackbody radiation learning in improving student’s critical thinking skills. The methods used were qualitative and quantitative with purposive sampling technique. We applied scientific based learning, where the experimental class used BSE interactive, while the control one used BSE non interactive. The results indicated that the learning used BSE interactive significantly and effectively could improve student's critical thinking skills at the 95% confidence level. Furthermore, there were significant differences in the critical thinking skills improvement between the experimental and control classes at the 95% confidence level with an N-gain value of 0.64 for the class that used interactive BSE and 0.53 for the class that used non-interactive BSE. The effect size value of interactive BSE utilization compared to non-interactive BSE was categorized in a high criteria with a Cohen's value of 1.78. These results were also supported by students' positive responses to interactive BSE utilization. Keywords: LCDS, critical thinking, blackbody radiation, BSE DOI: http://dx.doi.org/10.23960/jpf.v7.n1.201902